17-β Estradiol e resveratrol nos parâmetros bioquímicos e hematológicos de ratas ovariectomizadas submetidas a desmielinização pelo brometo de etídio - Martins, Danieli Brolo (2012)
Among the neurodegenerative diseases those involving the demyelination of the nervous system, such as multiple sclerosis (MS) that affects young and middle-aged adults, have great importance. Thus, the goal of this study was to evaluate 17-β estradiol and resveratrol as promising substances due to their antioxidant and anti-inflammatory actions, in the neuronal and non-neuronal cholinergic system, hematologic and behavioral parameters in ovariectomized rats under or not the demyelination by ethidium bromide (EB). In the article, animals were randomly assigned into three experimental groups of each age. Control groups consisted of adult (sham-A) and middle-aged (sham-MA) female rats, ovariectomized adult (OVX-A) and middle-aged (OVX-MA) rats without estrogen therapy reposition, and ovariectomized adult (OVX+E2-A) and middle-aged (OVX+E2-MA) rats treated with 17-β estradiol for 30 days. After this period, AChE activity and lipid peroxidation were measured in the brain, blood and lymphocytes.The results showed that the acetylcholinesterase (AChE) activity increased in the striatum (ST) of adult ovariectomized animals with and without estrogen replacement and middle-aged animals without replacement, as well as in the hippocampus (HP) of middle-aged animals without hormone replacement. The inhibition of the AChE activity occurred in the ST of adult animals with estrogen replacement, in the cerebral cortex (CC) of adult animals with estrogen replacement, as well as in middle-aged animals with and without hormone replacement. The AChE activity of whole blood increased in adult animals with estrogen supplementation and decreased in middle-aged animals without 17-β estradiol. The AChE activity of lymphocytes was stimulated in adult animals with or without estrogen replacement, and it was inhibited in the middle-aged animals without estrogen replacement. There was an increase in lipid peroxidation in brain structures of all adult ovariectomized animals and cerebellum and cerebral cortex of middle-aged ovariectomized animals. In the manuscripts, the animals were divided into 5 groups to evaluate the demyelination phase and 5 groups to evaluate the remyelination phase. In each phase the groups were: control sham rats; ovariectomized rats, not demyelinated; demyelinated ovariectomized rats; ovariectomized rats, not demyelinated, treated with 17-β estradiol; and demyelinated ovariectomized rats treated with 17-β estradiol. In the manuscript 1, we investigate the effects of 17-β estradiol supplementation under the parameters related to the AChE activity in the brain, total blood and lymphocytes, as well as serum butyrylcholinesterase (BuChE) activity for a period of 7 or 21 days.Ovariectomy associated with EB increased the AChE activity in all structures in demyelination and remyelination phases. Estrogen supplementation stabilized the AChE activity in demyelination and inhibited the enzyme activity in the CC, ST and cerebellum (CE) in the remyelination, besides preventing cognitive impairment induced by ovariectomy. The BuChE activity showed elevation in demyelination and inhibition in remyelination in demyelinated animals treated with 17-β estradiol. The blood AChE activity showed an increase in demyelinated, non-demyelinated with estrogen replacement and demyelinated with estrogen replacement animals in both phases. In the demyelination phase, the AChE activity of lymphocytes showed an increase in the demyelinated group, while other groups have shown inhibition of this enzyme activity. In the manuscript 2, we evaluated the effect of resveratrol on The complete blood count and AChE activity of lymphocytes. The use of resveratrol for seven days decreased the AChE activity in ovariectomized animals and animals with ovariectomy and demyelination, without changing the number of circulating cells, demonstrating that there is no correlation between the circulating lymphocytes and the AChE activity of these cells. Taken together, these results show that 17-β estradiol and resveratrol modulate the AChE activity. The effects of estrogen therapy are dependent on the age and brain structure to be analyzed. Low levels of estrogen are detrimental to the cholinergic system. The damaging effects of ovariectomy can be potentiated in the presence of demyelination, which are generally reversed by the use of 17-β estradiol. This study therefore contributes to a better understanding for the use of estrogen replacement therapy and alternative therapies, such as resveratrol, in menopausal conditions and, especially, neurodegenerative diseases, such as MS, which pursue the process of demyelination. If these results are ratified in humans, these substances can be considered new therapeutic strategies for women.